Acute Abdomen as a Clinical Presentation of COVID-19-Associated Multisystem Inflammatory Syndrome in Children - Elmira Hajiesmaeil Memar; Fatemeh Tahghighi; Sedigheh Yousefzadegan; Parisa Sadeghirad; Ashraf Mousavi; Ramin Zare Mahmoudabadi; Hossein Saeidi; Mehri Ayati; Sahar Naderi; Sara Memarian; Seyedmusa Zeinalabedin; Bahar Ashjaei; et al. (Case Reports in Surgery)
Background. On December 2019, a novel coronavirus disease (COVID-19) spread worldwide and became a pandemic. Multisystem inflammatory syndrome in children (MIS-C) due to cytokine release syndrome following COVID-19 presents with various manifestations. We hypothesize that one of the rare manifestations is acute abdomen. Case Presentation. In this case series, eight cases (five girls and three boys) of gastrointestinal (GI) involvement and acute abdomen were reported to be associated with the cytokine storm due to COVID-19 infection. All patients were of Iranian nationality (Caucasian ethnicity), with a mean age of 8.9 years (range 3.5–14). They all presented with fever and acute abdominal pain. Additionally, maculopapular rash and edema of the extremities were common presentations. Free fluid on abdominal ultrasound or computerized tomography (CT) scan was observed in all patients. All cases tested positive for COVID-19. In six cases, laparotomy or abdominal surgery was performed for a diagnosis of acute abdomen, but appendicitis was confirmed in only one case. None of the cases presented with phlegmon. Elevated serum lipase and amylase levels were noted in two cases. Seven patients received corticosteroid pulse therapy. Clinical symptoms improved after one or two doses, and all patients were discharged after 4 weeks of follow-up with no mortality or morbidity. Conclusion. Patients experiencing unexplained acute abdominal pain along with fever, skin rash, and peripheral edema, who had a history of COVID-19 infection prior to or during the episode of acute abdomen symptoms, should be considered to have MIS-C. Furthermore, methylprednisolone pulse therapy could be a safe treatment option, reducing hospitalization duration in this patient population.